Aerosol optical properties and mixing state of black carbon in the Pearl River Delta, China. (April 2016) - Tan, Haobo; Liu, Li; Fan, Shaojia; Li, Fei; Yin, Yan; Cai, Mingfu; Chan, P.W.
Abstract: Aerosols contribute the largest uncertainty to the total radiative forcing estimate, and black carbon (BC) that absorbs solar radiation plays an important role in the Earth's energy budget. This study analysed the aerosol optical properties from 22 February to 18 March 2014 at the China Meteorological Administration Atmospheric Watch Network (CAWNET) station in the Pearl River Delta (PRD), China. The representative values of dry-state particle scattering coefficient (σsp ), hemispheric backscattering coefficient (σhbsp ), absorption coefficient (σabsp ), extinction coefficient (σep ), hemispheric backscattering fraction (HBF), single scattering albedo (SSA), as well as scattering Ångström exponent (α) were presented. A comparison between a polluted day and a clean day shows that the aerosol optical properties depend on particle number size distribution, weather conditions and evolution of the mixing layer. To investigate the mixing state of BC at the surface, an optical closure study of HBF between measurements and calculations based on a modified Mie model was employed for dry particles. The result shows that the mixing state of BC might be between the external mixture and the core-shell mixture. The average retrieved ratio of the externally mixed BC to the total BC mass concentration (rext-BC ) was 0.58 ± 0.12, and the diurnal pattern of rext-BC can be found. Furthermore, considering that non-light-absorbing particles measured by a Volatility-Tandem Differential Mobility Analyser (V-TDMA) exist independently with core-shell and homogenously internally mixed BC particles, the calculated optical properties were just slightly different from those based on the assumption that BC exist in each particle. This would help understand the influence of the BC mixing state on aerosol optical properties and radiation budget in the PRD. Highlights: Aerosol optical properties were analysed using in-situ aerosol data. The external mixture will lead to high σsp and SSA. Non-carbon-containing particles make a slight difference in calculation of σsp, hbsp . The mixing state of BC may be between the external mixture and core-shell mixture.